GENERATION AND TOOTH CONTACT ANALYSIS (TCA) OF HYPOID GEAR DRIVE (Journal of Engineering, 2012)
The present work covers the Face-Hobbing method for generation and simulation of meshing of Face hobbed hypoid gear drive. In this work the generation process of hobbed hypoid gear has been achieved by determination of the generation function of blade cutter. The teeth surfaces have been drawn depending on the simulation of the cutting process and the head cutter motion. Tooth contact analysis (TCA) of such gear drive is presented to evaluate analytically the transmission error function for concave and convex tooth side due to misalignment errors. TCA results show that the gear is very sensitive to misalignment errors and the increasing of the gear teeth number decrease the transmission error for both concave and convex tooth sides and ensure smooth motion with low vibration.